Rickettsial infections are neglected causes of acute febrile illness in Teluk Intan, Peninsular Malaysia - Yuhana, MY; Hanboonkunupakarn, B; Tanganuchitcharnchai, A; Sujariyakul, P; Sonthayanon, P; Chotivanich, K; Pukrittayakamee, S; Blacksell, SD; Blacksell, SD; Paris, DH (MDPI, 2022)
Rickettsial infections are among the leading etiologies of acute febrile illness in Southeast Asia. However, recent data from Malaysia are limited. This prospective study was conducted in Teluk Intan, Peninsular Malaysia, during January to December 2016. We recruited 309 hospitalized adult patients with acute febrile illness. Clinical and biochemistry data were obtained, and patients were stratified into mild and severe infections based on the sepsis-related organ failure (qSOFA) scoring system. Diagnostic assays including blood cultures, real-time PCR, and serology (IFA and MAT) were performed. In this study, pathogens were identified in 214 (69%) patients, of which 199 (93%) patients had a single etiology, and 15 (5%) patients had >1 etiologies. The top three causes of febrile illness requiring hospitalization in this Malaysian study were leptospirosis (68 (32%)), dengue (58 (27%)), and rickettsioses (42 (19%)). Fifty-five (18%) patients presented with severe disease with a qSOFA score of ≥2. Mortality was documented in 38 (12%) patients, with the highest seen in leptospirosis (16 (42%)) followed by rickettsiosis (4 (11%)). While the significance of leptospirosis and dengue are recognized, the impact of rickettsial infections in Peninsular Malaysia remains under appreciated. Management guidelines for in-patient care with acute febrile illness in Peninsular Malaysia are needed.